Direct Myocardial Implantation of Human Fetal Stem Cells in Heart Failure Patients - Baltaytis, Y.V. (Проблемы криобиологии и криомедицины, 2005)
This study was made possible by an unrestricted grant from the Institute for Regenerative Medicine, Park House, Villa Nova, St. John, Barbados. The investigators wish to thank the Junta de Beneficencia de Guayaquil for providing facilities (Luis Vernaza Hospital) and support for the trial. The authors wish to thank Dr. Maritza Guerrero and Dr. Freddy Miranda, from the Pathology Department of Hospital L. Vernaza; Dr. Gustavo Rubio Calderon, Electron Microscopist from the Instituto Nacional de Higiene of Ecuador and Universidad Catтlica